Post-Cold War regionalism as explained in international relations: a critical essay - Meliadò, Fabrizio (Rivista di studi politici internazionali, 2022)
The design and implementation of preferential trade reforms – i.e. the partial or total liberalization of a country’s commercial regime at the bilateral or less-than-multilateral level – has undergone a significant increase since 1986. This phenomenon has been taken into account by leading schools of thought in the field of international relations, namely realism, liberalism and social constructivism, when investigating the strategic dynamics of economic integration. To a greater or lesser degree, scholars have conflicting explanations that add to the less disputed economic rationale for signing preferential trade agreements (Ptas). Nevertheless, scholars agree on the general proposition that the intensification of international commercial relations via Ptas is a dependent variable, as well as an important indicator, of a broader dramatic process of political, economic and social transformation that occurred throughout the world from the beginning of the 1980s. The aim of this essay is to illustrate the leading theoretical explanations for preferential trade reforms. The main findings show that the above-mentioned schools of thought provide good grounds for explaining the sequencing of bilateral trade agreements, but have to be read in the light which the political economy of Ptas sheds on the rationale for undertaking this type of reform. The essay provides a brief introduction to those theories in order to elicit further interest and research, as a fully comprehensive testing of the relevant insights would require an extensive empirical research.